A new interpretation for the garnet zoning in metapelitic rocks of the silgará formation, southwestern santander massif, colombia (2008)
A Barrovian sequence of the Silgará Formation at the southwestern Santander Massif, Colombian Andes, contains zoned garnets in which major and trace element zoning correlates with distribution of mineral inclusions, which may indicate that garnet growth rate varied through time and affected both composition and texture ofgarnets, although different garnet producing reactions have also played an important role in the chemical zoning of garent. However, a local metasomatism process associated to the action of late magmatic fluids associated to the emplacement of the Pescadero Pluton (external forcing mechanism) would be also considered. In particular, Ca, Mn and Y zoning patterns in some garnets correspond with inclusion-rich vs. inclusion-free zones, althoughthe distribution of inclusions does not correlate with chemical zoning (i.e., the same inclusions are found in Ca-rich and Ca-poor zones of the garnet). There is a similar lack of correlation with accessory phases (apatite, monazite, xenotime, ilmenite or rutile). In a garnet from the garnet-staurolite zone, a high Mn core containsabundant and randomly oriented apatite, monazite and ilmenite inclusions, while a euhedral low Ca mantle zone is inclusion-free and the high Ca / low Mn rim zone contains apatite, monazite and ilmenite aligned parallel to the margins of the garnet. Inclusions in garnet can also represent mineral phases were not completely consumed during garnet growth. Association of garnet zoning trends and patterns with inclusion distribution may help differentiatebetween processes that identically affect major-element zoning but that produced variable textures in the garnet.